Transformasi Tasawuf Modern Menurut Nasaruddin Umar Dan Relevansinya Dalam Masyarakat Multikulturalisme Di Indonesia - Hariyanto (Hikamia: Jurnal Pemikiran Tasawuf dan Peradaban Islam, 2024)
Abstract Sufism has undergone significant changes in line with the progress of time. New perspectives on understanding Sufism and its practices continue to emerge in the modern era. From Nasaruddin Umar's viewpoint, the transformation of modern Sufism includes a fresh understanding of the meanings of spirituality and religiosity, as well as changes in the way Sufi teachings are practiced. This research discusses Nasaruddin Umar's views on the transformation of modern Sufism and its relevance in the multicultural society of Indonesia.The study utilizes written works by Nasaruddin Umar and videos on his YouTube channel, analyzing them through content analysis methods to explore his perspectives and examine their relevance in addressing the phenomenon of multiculturalism in Indonesian society. In Nasaruddin Umar's perspective, Sufism needs to accommodate the changes occurring in society and provide relevant answers to the spiritual challenges faced in the context of multiculturalism. The results of this study indicate that the concept of modern Sufism from Nasaruddin Umar's perspective can positively contribute to responding to cultural conflicts in Indonesia. By instilling values of compassion and tolerance in Sufi practices, society can overcome divisions and embrace diversity as a positive strength. The transformation of Sufism not only reflects adaptation to the times but also serves as a source of inspiration to build a more harmonious and inclusive society. Keywords: Transformation, Modern Sufism, Multiculturalism, Nasaruddin Umar Abstrak Tasawuf telah mengalami perubahan penting seiring dengan kemajuan zaman. Perspektif-perspektif baru dalam memahami tasawuf dan praktik-praktiknya terus muncul di era modern. Dalam perspektif Nasaruddin Umar, transformasi tasawuf modern mencakup pemahaman baru tentang makna spiritualitas dan keberagamaan, serta perubahan dalam cara mengamalkan ajaran tasawuf. Penelitian ini membahas pandangan Nasaruddin Umar tentang transformasi tasawuf modern dan relevansinya dalam masyarakat Multikulturalisme di Indonesia. Studi ini menggunakan literature tertulis karya Nasaruddin Umar serta video-video dalam kanal youtube, lalu menganalisisnya dengan metode analisis konten untuk mengekplorasinya pandangan dan melihat kerelevanan pemikirannya dalam menghadapi fenomena masyarakat Multikulturalisme di Indonesia. Dalam pandangan Nasaruddin Umar, tasawuf perlu mengakomodasi perubahan-perubahan yang terjadi di masyarakat dan menyediakan jawaban-jawaban yang relevan untuk tantangan-tantangan spiritualitas yang dihadapkan dalam konteks masyarakat Multikulturalisme. Hasil dari studi ini menunjukkan bahwa konsep tasawuf modern perspektif tasawuf Nasaruddin Umar mampu memberikan kontribusi positif dalam merespons konflik-konflik kultural di Indonesia. Dengan menanamkan nilai-nilai kasih sayang dan toleransi dalam praktik tasawuf, masyarakat dapat mengatasi perpecahan dan merangkul keberagaman sebagai kekuatan positif. Transformasi tasawuf ini bukan hanya mencerminkan adaptasi terhadap zaman, tetapi juga menjadi sumber inspirasi untuk membangun masyarakat yang lebih harmonis dan inklusif. Kata Kunci: Transformasi, Tasawuf Modern, Multikulturalisme, Nasaruddin Umar